Usefulness of Non-Invasive Fetal RHD Genotyping towards Immunoprophylaxis Optimization - Blanco, Sebastian (2018)
Introduction: Since anti-D immunoprophylaxis given to D-negative pregnant women is a blood product, blood donations have an impact on the availability of prophylactic doses. The Pan American Health Organization reported, in June 2017, that less than half of blood donors are volunteers in Latin America and the Caribbean. In these countries, guidelines for use of anti-D prophylaxis are still controversial. The aim of this study was to demonstrate the convenience of a simple and cost-effectivene non-invasive prenatal diagnostic assay for anti-D prophylaxis optimization in multiethnic populations. Methods: Cell-free fetal DNA from plasma samples of D-negative pregnant women were analyzed by real-time PCR for simultaneous amplification of sequences of exons 5 and 10 of the RHD gene. Fetal RHD genotype was determined in 111 pregnant women. Neonates' phenotype was determined 72 h after birth. Results: Genotyping predicted fetal phenotype with 100% accuracy. Prenatal diagnosis showed 78% RHD-positive and 22% RHD-negative neonates. Conclusion: We demonstrated that, beyond the large genetic variation of the Rh system and the numerous D variants present in multiethnic groups, non-invasive fetal RHD genotyping using two sequences of the gene can be enough for clinical application in an admixed population. This robust technique of simple implementation allows to determine fetal RHD in maternal blood with high sensitivity, specificity, and accuracy. The introduction of fetal RhD genotyping as part of an antenatal screening program constitutes a reliable manner to optimize anti-D prophylaxis; however, it has not been implemented so far in most American countries.